2016
DOI: 10.1016/j.jaim.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double blind placebo controlled study of efficacy and tolerability of Withaina somnifera extracts in knee joint pain

Abstract: BackgroundRoot extracts of Withania somnifera (Ashwagandha) are known to possess analgesic, anti-inflammatory and chondroprotective effects. An aqueous extract of roots plus leaves of this plant has shown to yield higher percentages of withanolide glycosides and, accordingly, may possess better analgesic, anti-inflammatory and chondroprotective effects than root alone extracts.ObjectivesTo evaluate efficacy and tolerability of a standardized aqueous extract of roots plus leaves of W. somnifera in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 12 publications
2
16
0
1
Order By: Relevance
“…In clinical studies this medicinal plant has been shown to possess anti-microbial, anti-tumor, anti-inflammatory, anti-stress, cardioprotective, neuroprotective, anti-diabetic (Dar et al 2015), analgesic and chondroprotective properties (Ramakanth et al 2016). This medicinal plant is used in the treatment of various diseases like epilepsy, stress, Parkinson's and Alzheimer's disease, arthritis, rheumatism and to improve health and longevity (Pratibha et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies this medicinal plant has been shown to possess anti-microbial, anti-tumor, anti-inflammatory, anti-stress, cardioprotective, neuroprotective, anti-diabetic (Dar et al 2015), analgesic and chondroprotective properties (Ramakanth et al 2016). This medicinal plant is used in the treatment of various diseases like epilepsy, stress, Parkinson's and Alzheimer's disease, arthritis, rheumatism and to improve health and longevity (Pratibha et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…(asoka) 67 9.Acorus calamus L. (vacha) 68 10.Pentatropis capensis Linn. f.(kakanasa) 69 11.Embelia ribes Burm (vidanga) 70 12.Cassia occidentalis Linn (kasamarda) 71 13.Withania somnifera L. (ashwagandha) 72 14. Terminalia arjuna Roxb.…”
Section: Non Pharmacological Approachunclassified
“…Compared to placebo, root extract of W. somnifera in doses 250 mg and 125 mg showed significant reductions in mean modified WOMAC score, Knee Swelling Index and VAS scores for pain, stiffness and disability. 40…”
Section: Withania Somniferamentioning
confidence: 99%